Penerapan Gaya Kepemimpinan Birokrasi terhadap Kepuasan Kerja Pegawai Melalui Keterlibatan Pegawai Sebagai Variabel Intervening : Studi Kasus Dinas Perindustrian dan Perdagangan Provinsi Jambi - Riyandi Nurhawari Ahmad; Zulfina Adriani; Hendriyaldi Hendriyaldi (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the application of bureaucratic leadership styles on job satisfaction through employee involvement as an intervening variable (A Study of the Industry and Trade Office of Jambi Province). This research uses a quantitative method with data collection techniques by distributing questionnaires to 79 respondents selected using purposive sampling techniques. By using analysis techniques with SmartPLS version 4.0 and analyzing data using Structural Equation Modeling (SEM) techniques. The results of this study indicate that bureaucratic leadership style has a positive and significant influence on job satisfaction, Bureaucratic leadership style has a positive and significant influence on employee engagement, Employee involvement has a positive and significant impact on employee job satisfaction. Moreover, bureaucratic leadership style has a positive and significant influence on job satisfaction through employee engagement as an intervening variable at the Industry and Trade Office of Jambi Province. Testing the mediation effect shows that employee engagement can mediate the relationship between bureaucratic leadership style and job satisfaction, which means the higher the employee's engagement in taking responsibility for their work, the better the impact of bureaucratic leadership style on job satisfaction.